Political and Administrative Relations In The Role of Regional Head Officials: A Study on The Acting Governor of DKI Jakarta - Muhammad Reiza Fazri; Eko Prasojo (Journal Research of Social Science, Economics, and Management, 2024)
This journal article examines the dynamics of political and administrative relations within the context of the roles played by regional head officials. Specifically, it focuses on the case study of the Acting Governor of DKI Jakarta. The study delves into the intricate interplay between the political aspects of governance and the administrative responsibilities of regional leaders, shedding light on the challenges and opportunities faced by Acting Governors in Indonesia's capital city. By analyzing the experiences and strategies of the Acting Governor of DKI Jakarta, this research aims to contribute to a deeper understanding of the complex landscape of regional leadership. It explores how regional head officials navigate the political terrain while effectively managing administrative tasks, offering insights into the broader dynamics of governance in the region. This study serves as a valuable resource for scholars, policymakers, and practitioners interested in regional politics and administration, providing a case study that illuminates the roles and challenges faced by Acting Governors in Indonesia's dynamic political landscape.